Hybrid dual-curable cyanate ester/boron phosphate composites via sequential thiol-ene photopolymerization and thermal polymerization - KAHRAMAN, MEMET VEZİR (ELSEVIER SCIENCE SA, 2014)
The aim of this study was to improve hybrid dual-curable cyanate ester/boron phosphate composites via sequential thiol-ene photopolymerization and thermal polymerization for high performance applications such as aerospace and electronic devices. A novel 2,2'-diallylbisphenol A dicyanate ester (DA-BADCy) which is the allyl group containing cyanate ester was synthesized and characterized. DA-BADCy, silicon containing monofunctional thiol compound, trifunctional thiol compound and boron phosphate were cured using both ultraviolet (UV) and thermal methods. Using thiol-ene system, cyanate ester formulations, which are normally prepared at high temperatures, were prepared at room temperature. This study maintains ease of application for cyanate esters. Thermal stability, flammability and thermal conductivity of the samples were evaluated by thermogravimetric analysis (TGA), differential scanning calorimetry (DSC), limiting oxygen index (LOI) and laser flash method, respectively. The samples were characterized with the following analysis; gel content, water absorption capacity and stress-strain test. Hydrophobicity of the samples was determined by the contact angle measurements. Moreover, the surface morphology of the samples was investigated by a scanning electron microscopy (SEM-EDS). The obtained results prove that the composites have good thermal and mechanical properties and with the help of easier preparation techniques, they can be used in many applications such as aerospace, electronic devices, materials engineering. (C) 2014 Elsevier B.V. All rights reserved.
Keywords: Cyanate esters; Boron phosphate; Hybrid dual-curable; Thermal stability; Composites; Photopolymerization; ESTER; FUNCTIONALIZATION; MEMBRANES; POLYMERS; COATINGS; BLENDS; FILMS; UV